Blood lipids in young distance runners - Eisenmann, J. C.; Womack, C. J.; Reeves, M. J.; Pivarnik, J. M.; Malina, R. M. (Medicine & Science in Sports & Exercise, 2001)
Purpose: The purpose of this study was to examine the age-and sex-associated variation in blood lipids among young athletes. Methods: A mixed-longitudinal design was used to examine the development of blood lipids in competitive young distance runners followed from 1982 to 1985. Serial data included 99 annual measurements for 27 male subjects and 84 annual measurements for 27 female subjects aged 9-18 yr. Total cholesterol (TC), high-density lipoprotein (HDL-C), low-density lipoprotein (LDL-C), and triglycerides (TG) were determined by standard procedures. Results: In general, cross-sectional age group means showed that TC and LDL-C remained stable and HDL-C declined with age, especially in male subjects. TG increased with age. Age-related trends were statistically significant for HDL-C and TG in boys only (P < 0.05). TC and LDL-C were slightly greater in boys at all ages except 11, 15, and 17 yr (P > 0.05). HDL-C was similar between the sexes until 13 yr when values became greater in girls (3.2-13.8 mg.dL-1) (P < 0.05 in 17+ yr). No clear pattern of sex differences emerged for TG. Compared with the general population, blood lipids of young distance runners showed the following trends: 1) TC was above reference medians, 2) LDL-C tended to approximate or to be slightly above reference medians, 3) TG fluctuated about the reference medians, and 4) HDL-C was higher in distance runners compared to the reference medians before age 14 yr, but in the older age groups, especially male subjects, HDL-C either approximated or fell slightly below the reference medians. There was considerable variability in blood lipid levels among the runners. In 21 male and 18 female subjects with serial data for 3-5 yr, HDL-C declined 22.4 and 18.3 mg.dL-1 (P < 0.05), whereas TG increased 18.0 and 14.0 mg.dL-1 (P < 0.05 in female subjects only) in male and female subjects, respectively. Tracking coefficients over intervals of 3-5 yr were moderate to high (0.48-0.90), except for TG in male subjects (0.08). Conclusions: The results indicate that the development of blood lipids in young distance runners is similar to youth in the general population. In contrast to observations in adult endurance athletes, young distance runners did not possess a superior blood lipid profile except for HDL-C in the younger age groups.